Discovery Learning to Improve Science Learning Achievement of Class VI Elementary Students - Titi Ariyanti (Universitas Sebelas Maret, 2020)
The purposes this research was to determine that the aplication of the discovery learning model can improve the science learning achievement of grade VI elementary school students. The research conducted was Classroom Action Research (CAR) for three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, observation, observation and reflection. In the first cycle, the students who completed the test reached 60%, in second cycle 80%, and the third cycle 87%. These results indicate that the discovery learning model can improve the learning achievement of students in grade VI science subject matter at SDN Tepakyang.